Earnings Quality: The Role of Owners - Deden Tarmidi; Yuni Rosdiana; Helliana Helliana (Universitas Pendidikan Indonesia, 2023)
This study is a continued study in earnings quality, with the aim of analyzing the effect of ownership structure consisting of concentrated ownership, institutional ownership and foreign ownership on earnings quality. Manufacturing companies listed on the Indonesia Stock Exchange in 2014-2020 are the research population using purposive sampling. In addition to causal research by analyzing the respective effects of concentrated ownership, institutional ownership and foreign ownership on earnings quality, a sensitivity test was also conducted by comparing the effect of each independent variable on earnings quality with different measurement indicators, namely Performance Adjusted Accrual including Tax (PAiT), which is a new measurement developed by researchers and used in the main research model compared to the existing measurement, namely Performance Adjusted Dicretionary Accrual (PAccr). With the using of STATA in statistical analysis, this study found a negative effect of institutional ownership on earnings quality, while the opposite result was found on the effect of foreign ownership, although in this study there was no effect of concentrated ownership. These results are expected to contribute to investors who use earnings information in making investment policies, besides that the results of this study can be used as input for management in making company policies, especially in the preparation of financial information.